COMPARISON OF SAFER AND METRIC-BASED ACTUAL EVAPOTRANSPIRATION MODELS IN A SUBTROPICAL AREA OF BRAZIL - de Oliveira Ferreira Silva, Cesar; Lilla Manzione, Rodrigo; Luiz Albuquerque Filho, Jos´é (IRRIGA, 2019)
COMPARISON OF SAFER AND METRIC-BASED ACTUAL EVAPOTRANSPIRATION MODELS IN A SUBTROPICAL AREA OF BRAZIL CÉSAR DE OLIVEIRA FERREIRA SILVA1; RODRIGO LILLA MANZIONE2 E JOSÉ LUIZ ALBUQUERQUE FILHO3 1Agronomical Sciences Faculty, Universidade Estadual Paulista, Av. Universitária, 3780, Altos do Paraíso, 18610-034, São Paulo/SP, Brazil, cesaroliveira.f.silva@gmail.com. 2School of Sciences and Engineering, Universidade Estadual Paulista, Rua Domingos da Costa Lopes,780, Jd. Itaipu, 17602-496, Tupã/SP, Brazil, rlmanzione@gmail.com. 3Department of Hydrogeology, Institute of Technological Research (IPT), Av. Prof. Almeida Prado, 532, Cid. Universitária – Butantã, 05508-901, São Paulo/SP, Brazil, albuze@ipt.br. 1 ABSTRACT Remote sensing algorithms are well known to estimate surface energy fluxes in regional to global scales with low cost. The remote sensing approach has an advantage of estimating evapotranspiration (ET) on larger spatiotemporal scales when compared with traditional methods. This study compared the result of ET estimates from the “Simple Algorithm for Evapotranspiration Retrieving” (SAFER) and “Mapping Evapotranspiration at high Resolution with Internal Calibration” (METRIC) models on varied land uses of a subtropical area located in Southeast Brazil by using a image from the sensor OLI of LANDSAT-8. The results showed similarity of ET estimate from both models, although slight deviation especially at high ET values. It happened due differences as the need of anchor pixel in METRIC, which requires two points with extrem thermohydrological conditions in the same area. Minimum ground data requirement is the major advantage of the METRIC over the SAFER model. The maximum value, the sum and ET range by METRIC was higher than SAFER. This study has considered both models feasible for estimation of ET from satellite data in the study area. Keywords: remote sensing, modelling, superficial temperature, Landsat-8, agriwater. SILVA, C. O. F.; MANZIONE, R. L.; ALBUQUERQUE FILHO, J. L. COMPARAÇÃO DE MODELOS DE EVAPOTRANSPIRAÇÃO REAL SAFER E METRIC EM UMA ÁREA SUBTROPICAL DO BRASIL 2 RESUMO Algoritmos de sensoriamento remoto são conhecidos por estimar fluxos de energia de superfície em escalas regionais a globais com baixo custo. A abordagem de sensoriamento remoto tem a vantagem de estimar a evapotranspiração (ET) em escalas espaço-temporais maiores que os métodos tradicionais. Este estudo compara o resultado da estimativa de ET do “Simple Algorithm for Evapotranspiration Retrieving” (SAFER) e “Mapping Evapotranspiration at high Resolution with Internal Calibration” (METRIC) em variados usos da terra de uma área subtropical localizada no Sudeste do Brasil usando uma imagem do sensor OLI do satélite LANDSAT-8. Os resultados mostraram similaridade da estimativa da ET em ambos os modelos, embora houvesse desvio, especialmente em altos valores de ET. Isto é devido a diferenças como a necessidade de âncora de pixel no modelo METRIC, que necessita de dois pontos com condições termohidrológicas extremas em uma mesma área. A exigência mínima de dados terrestres é a principal vantagem do METRIC sobre o modelo SAFER. Esse estudo considerou ambos os modelos viáveis ​​para a estimativa de ET a partir de dados de satélite na área de estudo. Neste estudo, o valor máximo, a soma e a variação do ET pelo METRIC foram maiores que o do SAFER. Palavras-chave: sensoriamento remoto, modelagem, temperatura de superfície, Landsat-8, agriwater.